ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EFISIENSI PRODUKSI BENIH IKAN PATIN (STUDI KASUS PANDAWA LIMA FISHERIES FARM BOGOR) - Adam Purnama; Lilis Imamah Ichdayati; Rahmi Purnomowati (Departement of Agribusiness Faculty of Science and Technology, 2017)
The objectives of this research are; (1) to determine the factors effecting seed production of catfish in the Pandawa Lima Fisheries Farm Bogor, (2) to determine the elasticity of seed production of catfish in the Pandawa Lima Fisheries Farm Bogor, and (3) to determine the level of technical efficiency on hatchery operations of catfish in Pandawa Lima Fisheries Farm Bogor. The R/C analysis was employed to analyze income of catfish seed production for 30 cycles of production. Results showed that farm income is positive with a value of Rp 851,343.75 per cycle. The R/C value was 1.12 indicated that catfish hatcheries in Pandawa Lima Fisheries Farm is considered advantageous to cultivate.